Research on Factors Affecting Carbon Emission - Yang, Fan (International Journal of Natural Resources and Environmental Studies, 2024)
There are many factors affecting carbon emissions, involving energy consumption, industrial production, transportation and other aspects. In-depth study of these factors will not only help us understand the growth mechanism of carbon emissions, but also provide scientific basis for formulating effective emission reduction strategies. On the road of pursuing sustainable development, reducing carbon emissions and protecting the earth has become our common responsibility. In this paper, x indicators related to regional carbon emissions, economy, population and energy consumption and corresponding data are established to establish an indicator system. Secondly, the data is prepossessed before the establishment of the grey correlation model, which mainly includes the principal component analysis of the data and the selection of four indicators with large index scores. Finally, the grey correlation model is established to analyze the changes among related indicators and draw the conclusion of current situation analysis.